Method for characterizing evolution characteristics of pore structure of water-soluble induced salinized lacustrine carbonate rock

Through the water-dissolution-induced method, the evolutionary characteristics of pore structure of salted lake carbonate rocks were characterized, which solved the problem that it was difficult to obtain key parameters in the existing technology, and realized quantitative analysis of the impact of salt mineral dissolution on pore structure and guidance on the optimization of working fluid performance.

CN119595515APending Publication Date: 2025-03-11CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411888609.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively characterize the pore structure evolution characteristics of salted lake carbonate rocks caused by the dissolution of salt minerals, making it difficult to obtain key parameters such as porosity and permeability, and thus it is difficult to guide the optimization of reservoir protection performance of working fluids.

Method used

By using a water-soluble inducing method, a salted lake carbonate core sample was obtained, oil washing and drying were performed, and a standard plunger sample was prepared. Then, a high back pressure steady-state method was used to perform a displacement experiment, measure the fluid flow rate and ionic composition, and build a real-time porosity evaluation model and pore seepage evolution model for the dissolution process of salt minerals.

Benefits of technology

Quantitative analysis of the impact of salt mineral dissolution on the pore structure of salted lake carbonate rocks is achieved, providing real-time evaluation of porosity and permeability, helping to optimize the performance of the well-entered working fluid and guiding the improvement of reservoir protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595515A_ABST
    Figure CN119595515A_ABST
Patent Text Reader

Abstract

The invention relates to the field of drilling, completion and development of carbonate rock oil and gas reservoirs, and relates to a water-soluble induced salinized lacustrine phase carbonate rock pore structure evolution characteristic characterization method. The method comprises the following steps: preparing a standard plunger sample; acquiring various initial characteristics of the standard plunger sample; deionized water is adopted to carry out a standard plunger sample displacement experiment, the fluid flow at the outlet end is measured regularly, and ion components are analyzed; the standard plunger sample is dried, and various characteristics of the standard plunger sample after the displacement experiment are obtained; comparing various characteristics before and after the displacement experiment to obtain the influence of salt mineral corrosion on the pore structure of the salinized lacustrine carbonate rock; and calculating the real-time permeability and the real-time porosity, and constructing the pore permeability evolution model of the salinized lacustrine carbonate rock in the water-soluble process. According to the method, the influence of salt mineral dissolution on the pore structure of the salinized lacustrine phase carbonate rock can be quantitatively analyzed, and the real-time porosity evaluation model and the pore permeability evolution model of the rock in the salt mineral dissolution process are constructed, so that the performance optimization of the working fluid entering the well can be guided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of drilling, completion and development of carbonate oil and gas reservoirs, and to a method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lake-phase carbonate rocks. Background Art

[0002] Conventional carbonate rocks usually have a very low content of salt minerals, usually less than 10%, while saline lake carbonate rocks are deposited in a special salt lake environment and have a higher content of salt minerals, up to 30% or more. Since salt minerals are extremely unstable, saline lake carbonate rocks are very susceptible to dissolution in low-mineralization working fluids or atmospheric fresh water, which will significantly change the reservoir pore structure, physical properties, mechanics and other rock physical properties, potentially inducing serious reservoir damage and underground accidents.

[0003] Based on this, revealing the changes in the pore structure of carbonate rocks caused by salt mineral dissolution is of great significance for preventing and controlling reservoir damage induced by the interaction between salt minerals and working fluids or specifying corresponding measures. However, existing research or related patents have failed to provide how to characterize the pore structure evolution characteristics of saline lake-phase carbonate rocks caused by this, and it is difficult to obtain key parameters such as porosity and permeability, and it is difficult to effectively guide the optimization of working fluid reservoir protection performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide a method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lake-phase carbonate rocks, which can quantitatively analyze the influence of salt mineral dissolution on the pore structure of salinized lake-phase carbonate rocks, and construct a real-time porosity evaluation model and a pore permeability evolution model of rocks during the salt mineral dissolution process, which is helpful to guide the optimization of the performance of the working fluid entering the well.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lake-phase carbonate rocks, comprising:

[0006] Obtain a saltwater lake carbonate rock core, perform oil washing and drying pretreatment on the core, then make a standard plunger sample, and prepare deionized water;

[0007] Obtaining multiple initial characteristics of the standard plunger sample; the multiple characteristics include microscopic pore structure shape characteristics, porosity, permeability, initial pore structure characteristics from nanometer to hundred micrometer, displacement pressure, pore network spatial distribution and connectivity characteristics;

[0008] Based on the high back pressure steady state method, deionized water is used to carry out standard plunger sample displacement experiments. The back pressure is higher than the displacement pressure. When the liquid comes out from the outlet of the rock sample, the fluid flow rate at the outlet is measured regularly and the ion composition is analyzed. The experiment is stopped when the relative deviation of the permeability between the two tests is no more than 5%.

[0009] Dry the standard plunger sample, and then obtain various characteristics of the standard plunger sample after the displacement experiment; compare the various characteristics of the plunger sample before and after the displacement experiment to obtain the effect of salt mineral dissolution on the pore structure of saline lake carbonate rock;

[0010] The real-time permeability is calculated according to Darcy's law. A real-time porosity evaluation model during the displacement process is constructed based on the initial porosity of the standard plug sample and the ion composition and fluid flow rate during the displacement process. A porosity and permeability evolution model of the water dissolution process of saline lake-facies carbonate rocks is constructed based on the real-time permeability and the real-time porosity calculated by the real-time porosity evaluation model.

[0011] Furthermore, the microscopic pore structure shape characteristics, porosity and permeability of the standard plug samples before and after the displacement experiment were obtained; specifically:

[0012] Scanning electron microscopy was used to characterize the microscopic pore structure and shape characteristics of the standard plunger sample;

[0013] The porosity and permeability of the standard plug samples were tested using a porosity and permeability tester.

[0014] Furthermore, the initial pore structure characteristics and displacement pressure of the standard plunger samples at the scale of hundreds of nanometers to hundreds of micrometers before and after the displacement experiment were obtained; specifically:

[0015] A nitrogen adsorption test is used to obtain the nanoscale pore structure characteristic parameters of the standard plunger sample, and a high-pressure mercury injection test is used to obtain the pore structure characteristic parameters of the standard plunger sample from hundreds of nanometers to hundreds of micrometers and the displacement pressure.

[0016] Furthermore, the spatial distribution and connectivity characteristics of the pore network of the standard plug samples before and after the displacement experiment were obtained; specifically:

[0017] Micrometer-level CT scanning was carried out, and a 3D digital core model was constructed based on image processing to obtain the spatial distribution and connectivity characteristics of the pore network of the standard plug sample.

[0018] Furthermore, during the displacement experiment, the displacement pressure difference was 1-3 MPa, and the confining pressure was 1.5-3 MPa higher than the displacement pressure.

[0019] Furthermore, the real-time porosity assessment model is:

[0020]

[0021] In the formula, φ o, φ(t) are the porosity of the standard plunger sample at the initial and time t, respectively; V is the volume of the standard plunger sample; Q(t) is the flow rate of the fluid driven out at time t; C i (t) is the concentration of the i-th mineral dissolved in the fluid at the outlet at time t; ρ i is the density of the ith mineral.

[0022] Furthermore, by comparing various characteristics of the plunger samples before and after the displacement experiment, the effects of salt mineral dissolution on the pore structure of saline lake carbonate rocks were obtained; specifically:

[0023] The microscopic pore structure shape characteristics, pore network spatial distribution and connectivity characteristics before and after the displacement experiment were compared, and the changes in the pore type, shape and connectivity of the plunger samples after salt mineral dissolution were observed;

[0024] Compare the characteristic parameters of nanoscale pore structure before and after the displacement experiment, clarify the changes in the nanoscale pore size and distribution ratio of the standard plunger sample, and reveal the influence of salt mineral dissolution on the nanoscale pore structure of saline lake carbonate rocks;

[0025] Compare the characteristic parameters of pore structure at the scale of 100 nanometers to 100 micrometers before and after the displacement experiment, clarify the changes in displacement pressure, pore size, distribution ratio and connectivity between small pores and large pores of the pore system at the scale of 100 nanometers to 100 micrometers of the standard plunger sample, so as to reveal the influence of salt mineral dissolution on the pore structure at the scale of 100 nanometers to 100 micrometers of saline lake carbonate rocks;

[0026] By comparing the pore size and distribution ratio before and after the displacement experiment, it is clear that the salt mineral dissolution causes the nanopores of the standard plunger sample to transform into micropores.

[0027] After adopting the above technical solution, the present invention has the following beneficial effects:

[0028] The present invention conducts fluid displacement experiments to dissolve salt minerals in rocks, then qualitatively and quantitatively analyzes the impact of salt mineral dissolution on the pore structure of saline lake-phase carbonate rocks, and constructs a real-time porosity evaluation model for rocks during the salt mineral dissolution process based on the composition of dissolved ions. Finally, a porosity and permeability evolution model is established. The evaluation results are helpful to guide the optimization of the performance of the working fluid entering the well. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of the method for characterizing the pore structure evolution characteristics of water-dissolution-induced salinization lacustrine carbonate rocks of the present invention;

[0030] Figure 2 This is a graph showing the nitrogen adsorption test results before and after the dissolution of the salt minerals involved in the present invention;

[0031] Figure 3 It is a graph showing the results of high-pressure mercury injection testing of salt minerals before and after dissolution according to the present invention;

[0032] Figure 4 The porosity-permeability test result diagram of the salt mineral dissolution process involved in the present invention; wherein,

[0033] Figure 2 In the figure, (a) is the adsorption analysis curve; (b) is the pore size distribution curve;

[0034] Figure 3 In the figure, (a) is a capillary pressure curve; (b) is a pore size distribution curve;

[0035] Figure 4 In the figure, (a) is the relationship between porosity and permeability evolution over time; (b) is the relationship between porosity and permeability evolution. DETAILED DESCRIPTION

[0036] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments in conjunction with the accompanying drawings.

[0037] like Figure 1 As shown, a method for characterizing the pore structure evolution characteristics of water-dissolution-induced salinized lacustrine carbonate rocks comprises:

[0038] Step S1, obtaining a saltwater lake phase carbonate rock core, performing oil washing and drying pretreatment on the core, and then making a standard plunger sample (3-5 cm long, 2.5 cm in diameter), and preparing deionized water;

[0039] Step S2, obtaining multiple initial characteristics of the standard plunger sample; wherein the multiple characteristics include microscopic pore structure shape characteristics, porosity, permeability, initial pore structure characteristics from nanometer to hundred micrometer level, displacement pressure, pore network spatial distribution and connectivity characteristics;

[0040] Step S21, using a scanning electron microscope to characterize the initial microscopic pore structure shape characteristics of the standard plunger sample; using a pore-permeability tester to test the initial porosity and permeability of the standard plunger sample;

[0041] Step S22, using nitrogen adsorption test to obtain nanoscale pore structure characteristic parameters of the standard plunger sample, and using high-pressure mercury injection test to obtain pore structure characteristic parameters of the standard plunger sample from 100 nanometers to 100 micrometers and displacement pressure; through the results of nitrogen adsorption test and high-pressure mercury injection test, the multi-scale pore structure characteristics of saline lake phase carbonate rock from nanometers to 100 micrometers are jointly characterized;

[0042] Step S23, conduct micron-level CT scanning, construct a 3D digital core model based on image processing, and obtain the spatial distribution and connectivity characteristics of the pore network of the standard plunger sample.

[0043] Step S3, based on the high back pressure steady state method, a standard plunger sample displacement experiment is carried out using deionized water, the back pressure is higher than the displacement pressure, the displacement pressure difference is 1-3 MPa, and the confining pressure is 1.5-3 MPa higher than the displacement pressure. When the rock sample outlet discharges liquid, the outlet fluid flow rate is regularly measured and the ion composition is analyzed. The experiment is stopped when the relative deviation of the permeability between the two tests is no more than 5%.

[0044] Step S4, drying the standard plunger sample, and then obtaining various characteristics of the standard plunger sample after the displacement experiment;

[0045] Step S5, comparing various characteristics of the plunger sample before and after the displacement experiment to obtain the influence of salt mineral dissolution on the pore structure of saline lake carbonate rock.

[0046] Step S51, comparing the scanning electron microscope images before and after the displacement experiment to observe the changes in the pore type, shape and connectivity of the sample after the salt minerals are dissolved;

[0047] Step S52, comparing the nitrogen adsorption test results before and after the displacement experiment, clarifying the changes in the nano-scale pore size and distribution ratio of the samples, and revealing the influence of salt mineral dissolution on the nano-scale pore structure of saline lake carbonate rocks;

[0048] Step S53, comparing the high-pressure mercury injection test results before and after the displacement experiment, clarifying the changes in the displacement pressure, pore size, distribution ratio and connectivity between small pores and large pores of the sample's pore system at the scale of 100 nanometers to 100 micrometers, and revealing the influence of salt mineral dissolution on the pore structure of saline lake-phase carbonate rocks at the scale of 100 nanometers to 100 micrometers;

[0049] Step S54, combining nitrogen adsorption and high-pressure mercury injection testing to obtain the sample pore size distribution diagram, through comparative analysis of the pore size and distribution ratio before and after the experiment, to clarify the transformation of the sample nanopores into micropores due to salt mineral dissolution.

[0050] Among them, in step S5, the step of obtaining various characteristics of the standard plunger sample after the displacement experiment is the same as step S2. The nitrogen adsorption test results before and after the dissolution of the salt mineral involved are shown in Figure 2 The results of high pressure mercury injection tests on the salt minerals involved before and after dissolution are shown in Figure 3 .

[0051] Step S6, calculating the real-time permeability of the rock sample according to Darcy's law; constructing a real-time porosity evaluation model during the displacement process based on the initial porosity of the standard plunger sample and the ion composition and fluid flow rate during the displacement process;

[0052] The real-time porosity assessment model is:

[0053]

[0054] In the formula, φ o , φ(t) are the porosity of the standard plunger sample at the initial and time t, respectively; V is the volume of the standard plunger sample, cm 3 ; Q(t) is the flow rate of the fluid driven out at time t, ml / s; C i (t) is the concentration of the i-th mineral dissolved in the fluid at the outlet at time t, g / cm 3 ρ i is the density of the ith mineral, g / cm 3 .

[0055] Based on the real-time permeability and the real-time porosity calculated by the real-time porosity assessment model, a porosity and permeability evolution model of saline lake carbonate rock dissolution process is constructed.

[0056] In this example, the porosity-permeability test results of the salt mineral dissolution process involved are shown in Figure 4 It should be noted that Figure 4 R 2 is the correlation coefficient of the fitting curve.

[0057] The specific formula of the fitted real-time permeability is:

[0058] φ(t)=1.1572t 2 -0.1503t

[0059] The specific formula for fitting real-time porosity is:

[0060] k(t)=0.8405t 3.9892

[0061] The porosity and permeability evolution model of saline lake carbonate rock water dissolution process is constructed as follows:

[0062] k=0.01536(φ-6.3300) 1.888 +0.0102.

[0063] Specifically, this embodiment firstly uses nitrogen adsorption and high-pressure mercury injection testing to jointly characterize the multi-scale pore structure characteristics of saline lake-phase carbonate rocks from nanometers to hundreds of micrometers, and then uses CT scanning and image processing technology to reconstruct the three-dimensional image of the rock to characterize the spatial distribution characteristics of the reservoir pore network. By carrying out deionized water displacement experiments, the salt minerals in the rock are dissolved, and then the rock pore structure and porosity properties are changed. Then continue to use the above method to characterize the reservoir pore structure after salt mineral dissolution, revealing the influence of salt mineral dissolution on the pore structure of saline lake-phase carbonate rocks. At the same time, during the displacement process, the fluid flow is monitored in real time to calculate the real-time permeability, and the ion composition of the driven fluid is analyzed at the same time, and the composition of the dissolved minerals is inverted to estimate the real-time porosity, and finally establish a porosity-permeability evolution model of saline lake-phase carbonate rocks during salt mineral dissolution. The evaluation results are helpful to guide the optimization of the performance of the well working fluid.

[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks, characterized in that: include: Obtain a saltwater lake carbonate rock core, perform oil washing and drying pretreatment on the core, then make a standard plunger sample, and prepare deionized water; Obtaining multiple initial characteristics of the standard plunger sample; the multiple characteristics include microscopic pore structure shape characteristics, porosity, permeability, initial pore structure characteristics from nanometer to hundred micrometer, displacement pressure, pore network spatial distribution and connectivity characteristics; Based on the high back pressure steady state method, deionized water is used to carry out standard plunger sample displacement experiments. The back pressure is higher than the displacement pressure. When the liquid comes out from the outlet of the rock sample, the fluid flow rate at the outlet is measured regularly and the ion composition is analyzed. The experiment is stopped when the relative deviation of the permeability between the two tests is no more than 5%. Dry the standard plunger sample, and then obtain various characteristics of the standard plunger sample after the displacement experiment; compare the various characteristics of the plunger sample before and after the displacement experiment to obtain the effect of salt mineral dissolution on the pore structure of saline lake carbonate rock; The real-time permeability is calculated according to Darcy's law. A real-time porosity evaluation model during the displacement process is constructed based on the initial porosity of the standard plug sample and the ion composition and fluid flow rate during the displacement process. A porosity and permeability evolution model of the water dissolution process of saline lake-facies carbonate rocks is constructed based on the real-time permeability and the real-time porosity calculated by the real-time porosity evaluation model.

2. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: Obtain the microscopic pore structure shape characteristics, porosity and permeability of the standard plunger sample before and after the displacement experiment; specifically: Scanning electron microscopy was used to characterize the microscopic pore structure and shape characteristics of the standard plunger sample; The porosity and permeability of the standard plug samples were tested using a porosity and permeability tester.

3. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: Obtain the initial pore structure characteristics and displacement pressure of the standard plunger samples at the nanometer to hundred micrometer level before and after the displacement experiment; specifically: A nitrogen adsorption test is used to obtain the nanoscale pore structure characteristic parameters of the standard plunger sample, and a high-pressure mercury injection test is used to obtain the pore structure characteristic parameters of the standard plunger sample from hundreds of nanometers to hundreds of micrometers and the displacement pressure.

4. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: Obtain the spatial distribution and connectivity characteristics of the pore network of the standard plug sample before and after the displacement experiment; specifically: Micrometer-level CT scanning was carried out, and a 3D digital core model was constructed based on image processing to obtain the spatial distribution and connectivity characteristics of the pore network of the standard plug sample.

5. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: During the displacement experiment, the displacement pressure difference was 1-3 MPa, and the confining pressure was 1.5-3 MPa higher than the displacement pressure.

6. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: The real-time porosity assessment model is: In the formula, φ o , φ(t) are the porosities of the standard plunger sample at the initial and time t, respectively; V is the standard plunger sample volume; Q(t) is the flow rate of the fluid driven out at time t; C i (t) is the concentration of the i-th mineral dissolved in the fluid at the outlet at time t; ρ i is the density of the ith mineral.

7. The method for characterizing the pore structure evolution characteristics of water-soluble induced salinized lacustrine carbonate rocks according to claim 1, characterized in that: By comparing various characteristics of the plunger samples before and after the displacement experiment, we can understand the influence of salt mineral dissolution on the pore structure of saline lake carbonate rocks; specifically: The microscopic pore structure shape characteristics, pore network spatial distribution and connectivity characteristics before and after the displacement experiment were compared to observe the changes in the pore type, shape and connectivity of the plunger samples after salt mineral dissolution; Compare the characteristic parameters of nanoscale pore structure before and after the displacement experiment, clarify the changes in the nanoscale pore size and distribution ratio of the standard plunger sample, and reveal the influence of salt mineral dissolution on the nanoscale pore structure of saline lake carbonate rocks; Compare the characteristic parameters of pore structure at the scale of 100 nanometers to 100 micrometers before and after the displacement experiment, clarify the changes in displacement pressure, pore size, distribution ratio and connectivity between small pores and large pores of the pore system at the scale of 100 nanometers to 100 micrometers of the standard plunger sample, so as to reveal the influence of salt mineral dissolution on the pore structure at the scale of 100 nanometers to 100 micrometers of saline lake carbonate rocks; By comparing the pore size and distribution ratio before and after the displacement experiment, it is clear that the salt mineral dissolution causes the nanopores of the standard plunger sample to transform into micropores.